Some aspects of physico-chemical properties of chitosan in solutions and films / Elham S. Meftah Elgannoudi - Elgannoudi, Elham S. Meftah (2009)
This work is focused on studying the influence of temperature, concentration, shearing time and storage time on the rheological properties, i.e., the dynamic viscosity and shear stress as a function of shear rate of chitosan solubilized in the three selected solvents.Results showed that within the temperature range we studied (20oC to 50oC), apronounced shear thinning was observed. It was also found that all the solutions obeyed the Arrhenius equation. When the effect of concentration was studied, it was observed that the shear thinning behavior was more remarkable at the highest concentration (10 g L-1) for all solutions. The effect of shearing time on the dynamic viscosity of chitosan solutions did not show any significant differences at all shearing times studied in this study. Furthermore, more shear thinning behavior for chitosan in formic acid solutions,but less shear thinning for chitosan in acetic and propionic acids solutions were obtained with extending the period of storage to four months. A general decrease in viscosity with time for chitosan in formic acid solutions was observed while an increase in viscosity as a function of time was recorded for chitosan in acetic and propionic acids solutions at a constant shear rate.Chitosan (CS) films dissolved in three selected solvents were also investigated in this work, by employing thermogravimetric analyses (TGA), differential scanning calorimetry (DSC), scanning electron microscopy (SEM), atomic force microscopy(AFM), FTIR and mechanical properties. Results showed that the film made with acetic acid had the best thermal stability and lowest denaturation energy according to TGA and DSC measurements respectively. After a second run, the DSC curves showed small endothermic peaks at 186.20oC, 179.41oC and 171.43oC for chitosan films with formic,acetic and propionic acid solvents respectively. In addition, SEM measurements showed relatively smooth and homogenous surfaces for all films, which was confirmed by II AFM. The FTIR spectra of all chitosan films showed similar spectra with a little shift of some bands towards lower or higher wave numbers. Furthermore, chitosan film cast from acetic acid recorded the highest elongation at break, but the lowest tensile strength among the three types of film.